Andean lives : Gregorio Condori Mamani and Asunta Quispe Huamán - Condori Mamani, Gregorio, 1908- (University of Texas Press, 1996)
"Autobiographies first published in Cusco during the late 1970s in the original language. Sensitive and elegant translation, with detailed annotations, makes these life stories accessible to English-speaking readers"--Handbook of Latin American Studies, v. 57.